Simulasi Marker Beacon berbasis Mikrocontroller di Akademi Teknik dan Keselamatan Penerbangan Makassar - Atmia, Kurniaty; Aswar A., Muh. (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
Design simulation lab marker beacon as a means of using a microcontroller which acts as the brain of the components - components and Signal generator that acts as provide input in the form of a sinusoidal signal to the transmitter. When the transmitter sends a signal in the form of information will then be accepted by the receiver and forwarded to the Speaker. So as to produce a design that simulates the principle of a marker beacon equipment. This scheme aims to generate design simulation-based Marker Beacon Mikrokotroller in CASEA Makassar. The method used Design, Simulation, Breadboard, Transmitter, Receiver, Oscilloscopes, Signal Generator, Speaker, Arduino Uno. The result of this design provides a major benefit, namely Facilitate cadets to understand the working principle of Marker Beacon as well as providing an overview of the waves emitted by the marker beacon using osiloscope and increase knowledge ILS Marker Beacon particular.